2022
DOI: 10.7717/peerj.13758
|View full text |Cite
|
Sign up to set email alerts
|

Full-length 16S rRNA amplicon sequencing reveals the variation of epibiotic microbiota associated with two shrimp species of Alvinocarididae: possibly co-determined by environmental heterogeneity and specific recognition of hosts

Abstract: Shrimps of the family Alvinocarididae, endemic species to deep sea chemosynthetic ecosystems, harbor epibiotic microbes on gills which probably play important roles in the survival of the shrimps. Among them, Alvinocaris longirostris and Shinkaicaris leurokolos occupy different ecological niches within the same hydrothermal vent in Okinawa Trough, and A. longirostris also exists in a methane seep of the South China Sea. In this study, full-length 16S rRNA sequences of the gill associated bacteria of two alvino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…It has been shown that there are differences in concentration of chemical composition, temperature range and bacteria compositions between hydrothermal vent in Okinawa Trough and methane seep in the South China Sea (summarized in Hui et al, 2022). Therefore, excluding geographical factors and limited larval dispersal ability that may hinder the connectivity of populations, the snail P. glabra , as a common species in hydrothermal vent and methane seep, may have undergone local adaptive differentiation, which blocks the genetic exchange between populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that there are differences in concentration of chemical composition, temperature range and bacteria compositions between hydrothermal vent in Okinawa Trough and methane seep in the South China Sea (summarized in Hui et al, 2022). Therefore, excluding geographical factors and limited larval dispersal ability that may hinder the connectivity of populations, the snail P. glabra , as a common species in hydrothermal vent and methane seep, may have undergone local adaptive differentiation, which blocks the genetic exchange between populations.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotrophic microbes play important roles in the survival of animals in seep and vent. It has been revealed that more abundant methane‐oxidizing bacteria are in shrimp gill from the seep of the South China Sea than in the hydrothermal vent of Okinawa Trough, while sulfur‐oxidizing bacteria are dominant in the vent samples (Hui et al, 2022). Therefore, findings in this study imply that the selection of these outlier‐containing immune genes may be the result of the long‐term interaction of the snail P. glabra with different epibiotic, water or sediment microbe communities and other environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SMRT sequencing, a synthetic long-read sequencing technology based on full-length 16S rRNA, is widely used to study microbial communities in various environments, including food. It has been used to analyze microbial diversity in various samples ( Pootakham et al, 2017 ; Jeong et al, 2021 ; Hui et al, 2022 ; Liang et al, 2022 ). SMRT sequencing is advantageous over general Illumina sequencing because it provides accurate classification at a taxonomic level using full-length 16S rRNA sequences instead of short amplicons ( Mosher et al, 2014 ; Jeong et al, 2021 ); in this study, SMRT sequencing was used to confirm the microbial composition of fermented cabbage, including NM and USM samples.…”
Section: Discussionmentioning
confidence: 99%